SMES’ E-COMMERCE ADOPTION TOWARDS CONSUMER EXPERIENCE - Nuryanti Taufik; Faizal Haris Eko Prabowo; Allicia Deana Santosa; Andina Eka Mandasari (Jurnal Bisnis Manajemen, 2020)
This study aims to determine how the effect of e-commerce adoption on SMEs towards consumer experience in shopping online and its impact on repurchases. This research is a quantitative study with a survey method. The analytical tool used is Structural Equation Modeling. The sample size in this study is 205 respondents who have made transactions on the fashion SME e-commerce websites. The results showed that the better the adoption of e-commerce carried out by SMEs fashion, the better it is in providing a good experience for consumers, which ultimately made consumers repurchase on the website. This study provides new measurements of consumer responses in the form of experience after using SME e-commerce websites.